Analisis Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Polres Metro Bekasi Kota - Akhmad Imron Rosyadi; Sindu Depri Andika (Mulia Pratama, 2022)
Human Resources is the main factor in running a business in the organization. In this case, employees in government agencies have a very important role in carrying out state duties to serve the community. Therefore, work discipline and employee motivation are needed to achieve good employee performance. The goal to be achieved in this research is to find out how much influence Work Discipline and Work Motivation have on Employee Performance. The analytical method used in this study is multiple linear regression, the results of the data processing show the value of Y=1.378+0.770X1+0.193X2. The results of data processing on the coefficient of determination obtained R square value of 57.1%. That is, the variables of Work Discipline and Work Motivation contribute to the Employee Performance variable by 57.1% and the remaining 42.9 are influenced by other variables not examined in this study.